HUBUNGAN DUKUNGAN SUAMI DENGAN KONDISI FISIK DAN PSIKOSOSIAL IBU HAMIL REMAJA - Asrie Alifah; Ariani Fatmawati; Nina Gartika (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
The prevalence of teenage pregnancy in Indonesia is 7%. Adverse effects caused by pregnancy in adolescence are physical, psychological, and social complications, thus affecting the welfare of the mother. The purpose of this study was to determine the relationship between husband's support and physical and psychosocial conditions of teenage pregnant women. This study uses a correlative quantitative approach with a cross-sectional research design and sampling by consecutive sampling and data analyzed with the Spearman rank correlation test. Data collection used a husband's support questionnaire, physical condition of teenage pregnant women and a psychosocial condition questionnaire of teenage pregnant women. The total sample of 86 respondents with the characteristics of respondents who are pregnant women with an age range of 12-19 years, live in the Regency of Bandung, make ANC visits, have been married and live with their husbands. The analysis showed that the husband's support in the bad category was 37.2%, the physical condition of teenage pregnant women in the category of no interference 53.5%, and the psychosocial condition of teenage pregnant women in the category of no interference 62.8%. There is a relationship between husband's support and the physical condition of teenage pregnant women (p = 0.00) and the psychosocial condition of teenage pregnant women (p = 0.00). Husband's support for the physical condition of the mother can be seen in the ANC service and increase the acceptance and readiness of the mother in pregnancy in adolescence